Measurement technologies for precision positioning. Issue 2 (2015) - Gao, W.; Kim, S.W.; Bosse, H.; Haitjema, H.; Chen, Y.L.; Lu, X.D.; Knapp, W.; Weckenmann, A.; Estler, W.T.; Kunzmann, H.
Abstract Precision positioning of an object relative to a reference point is a common task in many activities of production engineering. Sensor technologies for single axis measurement, either linear or rotary, which form the fundamentals of measurement technologies for precision positioning, are reviewed. Multi-axis coordinate measurement methods such as triangulation and multilateration, as well as Cartesian and polar systems for specifying the position in a plane or three-dimensional (3D) space are then presented, followed by a discussion on traceability and standards. Some advanced applications of measurement technologies for precision positioning in manufacturing industries are also demonstrated.